The Role of the Food and Agriculture Service in Empowering Rice Farmers: Peran Dinas Pangan Dan Pertanian Dalam Pemberdayaan Pertani Padi - Triebuana Dewi Hayuningtyas; Lailul Mursyidah (Academia Open, 2021)
This study examines the empowerment of rice farmers in Kematan Tarik, in the agricultural process it is not uncommon to have several obstacles that often occur such as crop failure due to planthoppers and rats which often result in losses experienced by farmers. Therefore, there is a need for innovation related to the problems that occur in Tarik District. The purpose of this study is to determine the role of the Department of Food and Agriculture in providing innovation related to the problems that occur. This study uses a qualitative method of data obtained through observation, interviews. Data analysis techniques in this study are data collection, data reduction, data presentation and conclusion drawing.